IMPLEMENTASI KEBIJAKAN PERIZINAN PENYIARAN TELEVISI LOKAL DI PROVINSI GORONTALO - Rifka S Akibu (Publik : (Jurnal Ilmu Administrasi), 2015)
The aim of this research was to identify and to analyze the reality of the implementation of broadcasting license policy in Gorontalo Province and also to find out the obstacle factors of the process of realizing the local television permission in Gorontalo Province which studied based on the model theory of policy implementation of Van Metter and Van Horn by using variables: 1) Standard and policy target and the aims of the policy. 2) Source covers human resource and financial resource. 3) Implementer organization characteristic. 4) Communication between related organizations. 5) Disposition of implementer attitude, and 6) Social environment, economic and politic. This research was a qualitative research took sixth informant purposively. The result of this research showed that the implementation of broadcasting license policy in Gorontalo Provincedid not optimal yet because of: 1) the policy implementer had not conduct the policy based on the standard, 2) the source had not reached whether the human resource, money, communication and also policy implementer attitude maximum. The obstacle factor of optimum implementing of the broadcasting license policy was the policy implementer did not proactive in carried out the broadcasting license based on the time that has been determined and also there was lack of money support that caused the people involved to the policy cannot work maximum.